Township youth perceptions of poverty and unemployment in Cape Town, South Africa - Barrar, Erin M (Department of Social Development, 2014)
This study contributes to the understanding of how young adults living in Cape Town's townships experience poverty and unemployment in neighborhoods where both are prevalent. Unemployment is acknowledged to be a fundamental problem for township dwellers and yet the psychological repercussions on individuals in these communities remain largely understudied. While young people are the majority of South Africa's population, their voices frequently go unheard even with regards to issues that unduly affect them. In the last decade, a growing body of literature emerged using qualitative methods to address this concern. Quantitative analysis has shown that young adults - specifically African youth - bear the brunt of unemployment but research has yet to look closely at how unemployment shapes their expectations, attitudes and decision making. This research examines the effects of unemployment felt on an individual, psychological level as well as the contextual consequences of living in a neighborhood severely demoralized by widespread unemployment. Interviews with twenty youth between the ages of sixteen and thirty-two suggest that regardless of gender, age and class, (at least within the working class township community) young people are concerned with unemployment, which is often equated with poverty. In sharp contrast to the well-researched youth of the antiapartheid struggle whose lives were altered dramatically by the turbulence of those decades, these findings show that today's young adults in Cape Town's townships are ordinary young people growing up under particularly difficult circumstances, and with varying ability to mitigate the trials of their social worlds. Young adults in this sample are 'ordinary', in that when individually consulted, they cannot be categorized as a homogenous group. They have bold ideas about their future but their attention is often focused on the immediate. There are those who are ambitious and put their goals for personal success above all else. There are others who have high hopes but struggle both with their own decision making, and obstacles that set them back. Some are better-connected, some are more astute, and some are more at ease with their circumstances, willing to maintain the status quo rather than strive towards an abstract goal. Having little guidance from adults their influences are largely derived from their peer group, which emphasizes material culture and fitting in. Most believe in the importance of making 'good decisions' and aim to succeed but are easily frustrated by difficulties. They value the idea of education but do not always attend school or push themselves to excel. Even those who have achieved higher education sometimes question its merit in light of their disappointment in the job market. Despite assertions that there are 'no jobs' one finds that there are jobs but those available are less attractive when compared to the aspirations of these township youth. Their expected jobs vary with the level of education they have achieved however all desire employment outside of manual labor. This research shows that youth feel they can shape their futures but simultaneously expect their environment to hamper success. Success is largely viewed as a job or home that is 'better' than their parents, further distancing them from apartheid to which they feel no connection despite the lasting effects these policies have on the neighborhoods and institutions which continue to impair young people's growth. More specifically, despite aspirations for 'real' jobs in the formal market, the majority have ambivalent ideas for achieving these outcomes. Without examples of neighbors who have attained upward mobility, or access to information regarding opportunities outside of the township some youth's perseverance is stunted. The psychosocial implications of this issue have largely been ignored in South Africa. These interviews shed light on how the township environment interacts with and influences the decisions and attitudes of young adults. On one level, its isolation hinders communication regarding jobs, training or opportunities. In a social sense, the ubiquitous nature of unemployment stifles any sense of urgency, and the optimism of youth is often overshadowed by a sense of melancholy. There is a sense of defeat inhibiting the environment that affects young lives and limits their potential.